A new species of Mursia Desmarest, 1823 (Crustacea: Decapoda: Calappidae) from the Andaman Sea - Lai, Joelle C.y.; Galil, Bella (Zootaxa, 2006)
An examination of a series of calappid crabs collected from the Andaman Sea and deposited in the Zoological Reference Collection of the Raffles Museum, Singapore, revealed a new species, Mursia xianshengi n. sp. It differs from the closely related M. buwaya Galil & Takeda, 2004, in its larger size, wider carapace, and the anteriorly curved lateral spines of the carapace.